The Meaning Of The Verse Seribu Dinar In The Koran Surah Ath-Thalaq Verses 2-3: Roland Barthes Semiotic Application - YAPI, ALPIN (Jurnal Inen Paer (JIP), 2024)
The Koran is the primary source of Islamic teachings which contains and is rich in symbols. This article aims to find the denotative and connotative meaning related to the Thousand Dinar Verse (QS. At-Thalaq: 2-3). This article uses analytical descriptive methods and Roland Barthes' semiotic approach. Roland Barthes' theory is pursued in two steps, namely the first step is the linguistic system or denotation level, then the mythological system or connotation level. The results of the findings regarding the Verse One Thousand Dinars if you use these two steps, namely the denotation level is called sustenance, then the connotation level is called the path to opening up fortune in an unexpected way, then ease in difficulties, ease in making decisions and being able to sell your merchandise.